3PL firm's equity financing for technology innovation in a platform supply chain. (March 2021) - Fu, Hong; Ke, Ginger Y.; Lian, Zhaotong; Zhang, Lianmin
Highlights: We consider a platform supply chain with a supplier, a retailer, and a 3PL firm. We study supply chain coordination by deriving the optimal operational decisions. We find that the chain efficiency depends on the cost allocation among chain members. We check the robustness of our model by considering uncertain cost reduction. Abstract: Technologies have been driving improvements in logistics and transportation. Focusing on a third-party logistics (3PL) firm's technology innovations supported by external equity financing, we examine how the innovations can benefit the supply chain, and how the supply chain members should respond with coordinated operational decisions. More specifically, we consider a platform supply chain where a supplier sells a single product on an online platform provided by a retailer, and then hires a 3PL firm for transportation services. The 3PL firm may choose to raise capital through equity financing from external financial institutions, which can be used to support technology innovations to reduce the transportation cost. The financing decision of the 3PL interacts with operational decisions of the platform supply chain via possible cost savings. We start with investigating the supply chain coordination by characterizing the optimal operational decisions of the three firms under any given equity financing strategy. Acting non-cooperatively, the 3PL firm and the online retailer first determine the freight charge and revenue sharing respectively, in light of which the supplier's decision on the retail price. We then move to the 3PL firm internally and derive the optimal equity financing strategy. Our analytical results show that the supply chain efficiency is dependent on the cost allocation between the retailer and the other two firms, but independent of the cost allocation between those two firms. It is also revealed that the original shareholders of the 3PL firm always have a chance to benefit from an appropriate financing strategy, and the optimal financing strategy may depend discontinuously on supply chain parameters. Finally, we check the robustness of our model and show that all key findings remain unchanged when relaxing the deterministic cost reduction to an uncertain one.